Anisotropic critical behavior of current-driven skyrmion dynamics in chiral magnets with disorder - L Xiong; B Zheng; M H Jin; N J Zhou (New Journal of Physics, 2020)
The dynamic pinning effects are significant in manipulating skymions in chiral magnetic materials with quenched disorder. Through numerical simulations of the non-stationary current-driven dynamics of skyrmions with the Landau–Lifshitz–Gilbert equation, the critical current, static and dynamic critical exponents of the depenning phase transition are accurately determined for both adiabatic and non-adiabatic spin-transfer torques and with different strengths of disorder, based on the dynamic scaling behavior far from stationary. We find that the threshold current is insensitive to a small non-adiabatic coefficient of the spin-transfer torque, but dramatically reduced for a large one. The critical exponents indicate that the critical dynamic behavior is robust for different spin-transfer torques in the perpendicular component of the Hall motion, while exhibits a weak universality class in the direction of the driving current. The anisotropic behavior around the depinning phase transition provides a quantitative analysis of the drive-dependent skyrmion Hall effect in experiments. Further, the theoretical analysis using the Thiele’s approach is presented, and the critical current and the static exponents support the simulation results.